Securing Purchase Intention of E-Commerce Users: the Nomological Validity of Branding and Trust - Mahmud, Amir (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2022)
It is getting hard for digital brands to secure an edge over competitors; moreover, securing transaction deals. Amid E-Commerce offerings, brand awareness and image are strategically positioned in decision-making. Thus, this study explores this issue by analyzing the nomological validity of brand awareness and brand image on consumers’ trust and purchase intention. 165 response rates are secured and presented quantitatively by employing the variance-based PLS-SEM. The results support all hypotheses as well as the mediating effects. The brand image emerges as the most potential strategic position for managerial discretions upon building trust and purchasing decisions among e-commerce users.